Body image and eating disorders in aesthetic sports: A systematic review of assessment and risk - Berengüí, R.; Angosto, S.; Hernández-Ruiz, A.; Rueda-Flores, M.; Castejón, M. A. (Science & Sports, 2024)
Objective Conduct a systematic review to analyse the assessment of body image perception and risk of developing eating disorders, as a consequence of the practice of aesthetic sports.